THE NEED FOR GREATER AWARENESS OF LEGAL AID CLINICS IN FAMILY DISPUTE CASES: ADDRESSING ACCESS, AWARENESS, AND ASSISTANCE (International Journal of Food and Nutritional Sciences, 2023)
Family disputes can be emotionally and financially draining, often leaving vulnerable parties without adequate support. Legal aid clinics provide essential services for those unable to afford legal representation, offering guidance, counseling, and legal recourse in matters such as divorce, custody, and domestic violence. However, awareness of these services remains low, particularly among economically disadvantaged and rural populations. This paper examines the need for increased awareness about legal aid clinics in family dispute cases, analyzes the role of the judiciary in promoting access, and suggests initiatives for improving outreach. Through case studies and policy analysis, this paper highlights the benefits of legal aid clinics in ensuring justice and equitable treatment for all in family disputes.